I have an equation

$\displaystyle y =\frac{2x-5}{(3x+2)^2} $

so i have to differentiate it.

I think i am supposed to use the quotient rule

$\displaystyle (\frac {f}{g})' = \frac{gf'-fg'}{g^2}$

but i am confused about g'

In trying to differentiate it i come up with this

Expanded g.

$\displaystyle (3x+2)(3x+2)$

Then multiply out

$\displaystyle = 9x^2 +6x+6x+4$

$\displaystyle =9x^2+12x$

$\displaystyle =18x +12x$

so g' =20 x

Is this correct? I have a feeling ive done somthing wrong. Im just trying to work out g' so i can plug it into the equation.